Combinatorial reprogramming of lipid metabolism in plants: a way towards mass‐production of bio‐fortified arbuscular mycorrhizal fungi inoculants. Issue 1 (22nd October 2020) - Gargouri, Mahmoud; Bates, Philip D.; Declerck, Stéphane
Summary: Arbuscular mycorrhizal fungi (AMF) are among the most ancient, widespread and functionally important symbioses on Earth that help feed the world. Yet, mass‐production of clean (i.e. in vitro produced), safe and robust inoculum at affordable costs remains a critical challenge. Very recently, Luginbuehl et al. (2017) found that plants supply lipids to the symbiotic partner, thus ' providing the AMF with a robust source of carbon for their metabolic needs' . Hence, engineering plants for enhanced delivery of lipids to AMF could represent an innovative avenue to produce a novel generation of high‐quality and cost‐effective bio‐fortified AMF inoculants for application in agro‐ecosystems. Abstract : Mass‐production of clean (i.e. in vitro produced), safe and robust inoculum of arbuscular mycorrhizal fungi (AMF) at affordable costs remains a critical challenge. Engineering plants for enhanced delivery of lipids to AMF could represent an innovative avenue to produce a novel generation of high‐quality and cost‐effective bio‐fortified AMF inoculants for application in agro‐ecosystems.